Optimizing lettuce yields and quality by incorporating movable downward lighting with a supplemental adjustable sideward lighting system in a plant factory - Mutombo Arcel, Mulowayi; Yousef, Ahmed Fathy; Shen, Zhen Hui; Nyimbo, Witness Joseph; Zheng, Shu He (PeerJ, 2023)
Background Lettuce is a vegetable that is increasingly consumed globally, given its nutritional quality. Plant factories with artificial lighting can produce high-yield and high-quality plants. High plant density in these systems speeds up leaf senescence. Wasted energy and lower yield raised labor expenses are some of the bottlenecks associated with this farming system. In order to increase lettuce yields and quality in the plant factory, it is essential to develop cultivating techniques using artificial lighting. Methods Romaine lettuce was grown under a developed “movable downward lighting combined with supplemental adjustable sideward lighting system” (C-S) and under a system without supplemental sideward lighting (N-S) in a plant factory. The effects of C-S on lettuce’s photosynthetic characteristics, plant yield, and energy consumption relative to plants grown under a system without N-S were studied. Results Romaine lettuce growth and light energy consumption in the plant factory were both influenced favorably by supplementary adjustable sideward lighting. The number of leaves, stem diameter, fresh and dry weights, chlorophyll a and b concentration, and biochemical content (soluble sugar and protein) all increased sharply. The energy consumption was substantially higher in the N-S treatment than the C-S.
Keywords: Control system; LED; Leaf senescence; Photosynthetic rate; Lettuce yield; Photo-morphology